Kanserli hastalarda yorgunluk - (:unkn) unknown (My University, 2009)
Yorgunluk, kanserli hastalar tarafından en sık deneyimlenen, kişiyi gucsuz duşuren bir semptomdur. Kanser ve tedavisine balı olarak gorulen yorgunluk, hastaların fiziksel, ruhsal ve sosyal işlevini bozan, yaşam kalitesini duşuren, yaygın gorulen bir belirtidir. Hemşireler icin, kansere balı yorgunluun patofizyolojisini, etiyolojisini, değerlendirmesini ve tedavisinde kullanılan farmakolojik-nonfarmakolojik yontemleri bilmek yorgunluk yonetiminde onemlidir.

Fatigue is one of the most common and debilitating symptoms experienced by patient with cancer. Fatigue, which is occurred as a consequence of the cancer itself and as side effect of cancer treatment, impacted of physical- emotional-social functioning, patient’s quality of life, is common symptom. It is important to understand the pathophysiology, etiology, assessment of fatigue, the pharmacologic and nonpharmacologic methods to management of fatigue for nurses.
Fatigue in patients with cancer
Keywords: Hemşirelik